Clash of convictions: conventional banking vs Islamic banking - Muneeza, Aishath; Wisham, Ismail; Hassan, Rusni (LexisNexis Malaysia Sdn Bhd, 2010)
Malaysia is a religiously and ethnically versatile country with a dual legal structure. Essentially, Malaysia's banking system is plural and thus, two different sets of legal systems work at the same time. The semi-permanent conventional banking system has been leveled off by the Islamic banking system which emerged only in 1983. Whether accepted or not, the dual system which emerged only in 1983. Whether accepted or not, the dual system in the society has created challenges and clashes between the two, and these must be addressed and dealt with properly, so as to trim down such clashes to a minimum. Several quarrels exist between conventional and Islamic banking laws; some which arise due to the application of common law or conventional law to justify problems in Islamic banking system. The impact of this is huge; as applying the same legal principles enforced in the conventional banking system to adjudicate conflicts in the Islamic banking system - which has different economic principles - does not work at all. Islam contends for a fair distribution of profits and loss and bans questionable activities unlike the conventional banking capitalistic belief that winner takes all.